Exploring the usage and impact of urban sanitation tools targeting low- and middle-income countries - Furlong, C.; Mugendi, A.; Brdjanovic, D. (Frontiers in Environmental Science, 2023)
In recent years the number of tools developed to help advance sustainable urban sanitation coverage in low- and middle-income countries has increased significantly, yet no study has been undertaken to determine their usage or impact. This paper explores the usage and impact of four urban sanitation tools: Shit flow Diagram (SFD), City Service Delivery Assessment (CSDA), SaniPath, and Citywide Planning Tool. A mixed methods approach was used which included a questionnaire (n=87) and interviewing the tools developers (n=5) and users (n=25). There was a high awareness of three of the tools (86%, n=87), but relatively low usage (53%, n=87). The questionnaire respondents and interviewees confused the Citywide Planning Tool with other tools, so no usage was found. The CSDA and SaniPath were being used beyond the groups that developed them and by their targeted group, but the main users were found to be researchers in academia. There was evidence that SFDs and CSDAs were evolving beyond their original scope, which was attributed to their use in academia. Their use in academia should not be dismissed as they may lead to future usage and impact. Although impact will take time and it is difficult to directly attribute impact to a specific tool, evidence of the impact of the SFD and SaniPath was found. This impact demonstrates how these tools can lead to improvements in urban sanitation. This study also highlights the need for further research into the drivers of tool usage.